2012
DOI: 10.1021/cb300059z
|View full text |Cite
|
Sign up to set email alerts
|

Genetically Encoded Photo-cross-linkers Map the Binding Site of an Allosteric Drug on a G Protein-Coupled Receptor

Abstract: G protein-coupled receptors (GPCRs) are dynamic membrane proteins that bind extracellular molecules to transduce signals. Although GPCRs represent the largest class of therapeutic targets, only a small percentage of their ligand-binding sites are precisely defined. Here we describe the novel application of targeted photo-cross-linking using unnatural amino acids to obtain structural information about the allosteric binding site of a small molecule drug, the CCR5-targeted HIV-1 co-receptor blocker maraviroc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
62
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 65 publications
(65 citation statements)
references
References 27 publications
(52 reference statements)
3
62
0
Order By: Relevance
“…In fact, the position of the C-␤ atom of Y108 suggests that it is indeed located close enough to VVC for an interaction to be possible. In previous mutagenesis-based studies, the residues identified as interacting with VVC and MVC were similar to those predicted by our models, although there were subtle differences in the extent and nature of the interactions of the two inhibitors with individual residues (45)(46)(47). Overall, MVC and VVC are predicted to have a common binding site within the TM bundle and to contact similar residues, albeit with perhaps some differences in their modes of binding.…”
Section: Affinity Of Vvc For G-protein-coupled and Uncoupled Receptorssupporting
confidence: 75%
“…In fact, the position of the C-␤ atom of Y108 suggests that it is indeed located close enough to VVC for an interaction to be possible. In previous mutagenesis-based studies, the residues identified as interacting with VVC and MVC were similar to those predicted by our models, although there were subtle differences in the extent and nature of the interactions of the two inhibitors with individual residues (45)(46)(47). Overall, MVC and VVC are predicted to have a common binding site within the TM bundle and to contact similar residues, albeit with perhaps some differences in their modes of binding.…”
Section: Affinity Of Vvc For G-protein-coupled and Uncoupled Receptorssupporting
confidence: 75%
“…In addition to CB1 (7,8), SuperBiHelix has been applied successfully to the adenosine A 3 receptor (16) and other adenosine receptors (22), serotonin 5-HT2B and 5-HT2C receptor (25), the histamine H3 receptor (26), the CCR5 receptor (27,28), TAS2R38 bitter taste receptor (29), and the V2 vasopressin receptor (30). The predicted GPCR structures in these studies were validated by predicting the binding sites and energies for known series of ligands and comparing with experimental mutagenesis, binding, and/or functional data.…”
Section: Discussionmentioning
confidence: 99%
“…It is restricted to residues in close vicinity to the reactive moiety of AzF. This prerequisite not only abolishes false-positive hits, it can also be utilized to map interactions, as shown recently for different examples of receptors and ligands in the mammalian system (57,58).…”
Section: Discussionmentioning
confidence: 99%